Recent Advances in Addressing J-V Curve Hysteresis in Perovskite Solar Cells - Benfatima, Khalil; Zazi, Khalida; Bah, Abdellah (European Journal of Applied Sciences, 2025)
Despite their incredible potential as replacements for traditional silicon cells, perovskite solar cells (PSC) are prone to J-V curve hysteresis which prevents accurate performance measurement. This paper synthesizes recent research relevant to understanding this issue. The primary causes are identified as ion migration, charge trapping, and ferroelectric effects within the perovskite. Studies have shown that doping solutions to improve crystal quality and defects, in addition to interface engineering to modify or replace the charge transport layers, show effective results. Furthermore, new techniques can help estimate hysteresis more accurately. While these solutions are remarkable, further real-life conditions testing, as well as economic and environmental simulations remain to be done to assess the scalability of production of these cells with new materials. Advances in hysteresis research are critical to the successful exploitation of PSCs in the future.